Ship Maneuverability Experiments on Open Water with Rudder Model Variations: Case Study of SPB-XXOO - Hutama, Rizka Arie; Aryawan, Wasis Dwi; Sugita, Ericza Damaranda (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2020)
Ship maneuverability is important to study because it affects safety. Moreover, if the ship operates in a narrow shipping lane, as experienced by SPUB that operated in Musi River. This research focuses on the experimental process of SPUB maneuvers in open water, especially for the turning circles' movement. The experiment was conducted using a prototype, model SPB-XXOO, which was equipped with components of the instrumentation system such as data logger and propulsion system. Both are integrated into the remote control and computer to perform control functions, calculations, data logging, and data transfer through the wireless communication system. The main controller of the propulsion system is an implanted program to deflect the rudder automatically. Three rudder models with variations in aspect ratios of 1.10, 1.65, and 2.20, also two variations of the rudder angle; 30o and 35o are used to test the model. GPS does the data acquisition process for each experimental process. Based on the analysis of the rudder model's effect, it was found that a rudder with a large aspect ratio provides better performance than a lower aspect ratio. The average increase in the maneuver performance of the rudder with the smallest to the most significant aspect ratio is 17.345%.